Preserving Johor’s Independence in The 1880s: The Question of Abu Bakar’s Personal Standing - Abdullah, A Rahman Tang (Paramita: Historical Studies Journal, 2024)
Abstract: There is a tendency among historians to argue that the main factor in the preservation of the independence of Johor was the political talent of its ruler, Abu Bakar, in resisting pressure from the Singapore authorities. Many would argue that Abu Bakar was successful in resisting the pressures from Frederick Weld, the Governor of the Straits Settlements, to extend the British Residential system to Johor in the mid-1880s by establishing diplomatic relations with the London authorities, notably the Colonial Office, which was used to play off Singapore. This article focuses on the issue surrounding Abu Bakar’s (1862-1895) personal standing in preserving Johor’s independence in the 1880s, which will include a discussion on the friction that existed between him and Sir Frederick Weld, the Governor of the Straits Settlements (1880-1887) in Singapore. The methodology employed in this paper is based on a historical presentation on the subject of discussion with the utilisation of primary sources complemented with secondary sources. The primary sources are mainly derived from the official British correspondence found in the Colonial Office Records, Volume 273 (CO273). The incorporation of the secondary sources refers to the existing writings by historians associated with the subject in discussion for the purpose of interpretation. This paper attempts to present the argument that Abu Bakar’s personal credibility in resisting pressure was effective only as long as he conformed to suit the British colonial interests that were preoccupied with economic rather than political means. Hence, I assert that Abu Bakar was able to preserve Johor’s internal independence as long as Johor remained economically dependent on Singapore and Abu Bakar was willing to abandon his economic means inside and outside Johor in conformity to the British colonial policy in the Malay states.Abstrak: Artikel ini berfokus pada isu seputar kedudukan pribadi Abu Bakar (1862-1895) dalam melestarikan kemerdekaan Johor pada tahun 1880-an, yang akan mencakup diskusi tentang gesekan yang terjadi antara dirinya dan Sir Frederick Weld, Gubernur Straits Settlements (1880-1887) di Singapura. Metodologi yang digunakan dalam makalah ini didasarkan pada penyajian historis tentang subjek diskusi dengan pemanfaatan sumber-sumber primer yang dilengkapi dengan sumber-sumber sekunder. Sumber-sumber primer sebagian besar berasal dari korespondensi resmi Inggris yang ditemukan dalam Colonial Office Records, Volume 273 (CO273). Penggabungan sumber-sumber sekunder mengacu pada tulisan-tulisan yang ada oleh para sejarawan yang terkait dengan subjek yang dibahas untuk tujuan interpretasi. Makalah ini mencoba menyajikan argumen bahwa kredibilitas pribadi Abu Bakar dalam melawan tekanan hanya efektif selama ia menyesuaikan diri dengan kepentingan kolonial Inggris yang lebih mementingkan cara-cara ekonomi daripada cara-cara politik. Oleh karena itu, saya menegaskan bahwa Abu Bakar mampu mempertahankan kemerdekaan internal Johor selama Johor tetap bergantung secara ekonomi pada Singapura dan Abu Bakar bersedia meninggalkan cara-cara ekonominya di dalam dan di luar Johor sesuai dengan kebijakan kolonial Inggris di negara-negara Melayu.